Malaysian student’s attitude towards organic food buying behaviour - Basha, Mohamed Bilal; Yesufu, Lawal; Busari, Saheed Abdullahi; AlHafidh, Gail; Alali, Fatima Sultan Khalfan Helis (Springer Nature, 2023)
In many developing countries export earnings account for a large percentage of the country Gross Domestic Product (GDP), government revenues and expenditures and public investment. High dependency on a limited number of commodities for export increases the economy vulnerability to price fluctuations in the global markets. Not only instability in export earnings reduces the ability of the economy to finance development, but also increases uncertainty about future growth. Economic diversification underscores the importance of productivity growth to balance development and reduce dependency on international markets.